Instrumented strength assessment in typically developing children and children with a neural or neuromuscular disorder: A reliability, validity and responsiveness study - Verreydt, Ineke; Vandekerckhove, Ines; Stoop, Elze; Peeters, Nicky; van Tittelboom, Vanessa; Van de Walle, Patricia; Van den Hauwe, Marleen; Goemans, Nathalie; De Waele, Liesbeth; Van Campenhout, Anja; Hanssen, Britta; Desloovere, Kaat (Frontiers in Physiology, 2022)
The aim of this study was to determine the clinimetric properties, i.e., reliability, validity and responsiveness of an instrumented strength assessment in typically developing (TD) children and children with cerebral palsy (CP) and Duchenne muscular dystrophy (DMD). Force (N), torque (Nm) and normalized torque (Nm/kg) were defined for maximal voluntary isometric contractions (MVICs) of the lower limb muscles using a pre-established protocol. Intraclass correlation coefficient (ICC), standard error of measurement (SEM) and minimal detectable change (MDC) of TD children (n=14), children with CP (n=11) and DMD (n=11) were used to evaluate intra-rater reliability for the three cohorts and the inter-rater inter-session as well as inter-intra intra-session reliability for TD children. Construct validity was assessed by comparing MVICs in TD children (n=28) to children with CP (n=26) and to children with DMD (n=30), using the Kruskal Wallis and post-hoc Mann-Whitney U tests. Responsiveness was investigated by assessing changes in MVICs following a strengthening intervention in CP (n=26) and a 1 and 2 year follow-up study in DMD (n=13 and n=6, respectively), using the Wilcoxon signed-rank tests. The overall intra-rater reliability, was classified as good to excellent for 65.1%, moderate for 27.0% and poor for 7.9% of the measures (47.6%, 76.2% and 71.4% good-excellent; 28.6%, 23.8% and 28.6% moderate; 23.8%, 0% and 0% poor in TD, CP and DMD, respectively), while ICC values for TD children were slightly lower for inter-rater intra-session reliability (38.1% good-excellent, 33.3% moderate and 26.6% poor) and for inter-rater inter-session reliability (47.6% good-excellent, 23.8% moderate and 28.6% poor). Children with CP and DMD were significantly weaker than TD children (p<0.001) and the majority of these strength differences exceeded the MDC. Children with CP significantly improved strength after training, with changes that exceeded the SEMs, whereas only limited strength decreases over time were observed in the DMD cohort. In conclusion, the investigated instrumented strength assessment was sufficiently reliable to confirm known-group validity for both cohorts and could detect the responsiveness of children with CP after a strength intervention. However, more research is necessary to determine the responsiveness of this assessment in children with DMD regarding their natural decline.